The Dynamics of Student Mental Health in perspective Psychology of Islamic Education: Factor Analysis and Psychological Spiritual Development Strategy - Farhan, Muhammad; Shobahiya, Mahasri (Al-Fikru: Jurnal Ilmiah, 2024)
Students’ mental health is often dynamic due to various factors both internal and external. In this regard, this research aims to analyze the dynamics of students’ mental health in the perspective of Islamic education psychology at the Assalaam Modern Islamic Boarding School. The focus of the research is on the factors and strategies of psychological spiritual development. This research uses phenomenological qualitative methods to uncover. Data collection methods include interviews, participatory observation, and documentation. The results revealed the complexity of the santri’s psychological challenges, including academic pressure, identity conflicts, and socio-spiritual dynamics in the pesantren environment. The research found that environmental factors, educational patterns, and social interactions have substantial significance to the mental health of santri. The strategies applied in coaching are integrative counseling guidance, strengthening resilience, and continuous mentoring. This study produces a comprehensive intervention model that integrates psychological approaches with spiritual guidance, aiming to optimize the mental health and character development of santri within the framework of Islamic religious education.